Glycemic index and cancer - Ciok, Janusz; Dolna, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2005)
Diet is implicated in the origin of many cancers, with risk factors for the disease including reduced consumption of vegetables, dietary fiber, and increased consumption of red meat and animal fat. Several hypotheses have been developed to explain these associations. Recently insulin resistance was attributed as a factor predisposing to several cancers, for example colon, breast and pancreatic cancer. The evidence sug- gests that diets with a high glycemic index lead to insulin resistance with hyperinsulinemia. The glycemic index is a ratio which ranks carbohydrate-containing foods depending on how they affect blood glucose levels. It is calculated by comparing single food product’s influence on glycemia after eating with a glycemic effect of reference food, glucose, set to equal 100. We review the evidence from observational, epidemiological, and experimental animal studies linking high glycemic index diet with insulin resistance and carcinogenesis. Probably insulin-like growth factor (IGF) system plays an indirect role in this effect enhancing tumor cell proliferation. The results of many epidemiological studies confirm that high glycemic index diet is related to the increased risk of some cancers. More research is needed to recognize the mechanisms linking high glycemic index diet and cancer and to specify nutritional guidelines to prevent cancer.